Diversity and microbial community in new dark earth soils in Tailândia-Pará, Brazil - Sávia Poliana da Silva; Diocléa Almeida Seabra Sillva; Maria de Lourdes Pinheiro Ruivo; Ismael de Jesus Matos Viégas; Rosigrêde Lima da Silva; Pedro Vitoriano de Araújo Júnior; Heráclito Eugênio Oliveira da Conceição (Semina: Ciências Agrárias, 2013)
Anthropogenic Dark Earth, one of the most fertile soils in the world, often occur in the Amazon region and shows the effect of intensive occupation of land by pre-Columbian indigenous peoples. By studying Dark Earth, it is possible to develop techniques to reproduce its fertility. This study aimed to reproduce Indian Dark Earth through the use of vegetable and animal waste deposited on oxisol and to survey the biodiversity of the microbial community of this “New Dark Earth” (TPN) in the municipality of Tailândia-Pará, Brazil, during the dry and rainy seasons. The experimental design was a randomized block design with 4 replicates, in an area of 3 ´ 3 m, with 2 m separating them. Combinations of coal (C), waste sawdust (RPS), shredded wood blade waste (RLT), bone residue (RA), as well as blood and fat (S) were used for the following treatments: 1 (C), 2 (RPS), 3 (RLT), 4 (RA), 5 (C + RPS), 6 (C + RLT), 7 (C + RA), 8 (RPS + RLT), 9 (RPS + RA), 10 (RLT + RA), 11 (C + RPS + RLT), 12 (C + RLT + RA), 13 (RPS + RLT + RA), 14 (C + RPS + RLT + RA), 15 (C + RPS + RLT + RA + S), 16 (Control), and 17 (C + RPS + RA). The bacterial population was higher than the fungal population in the 2 study periods, and the rainy season increased the fungal population. The predominant fungi were of the genus Aspergillus, Penicillium, Sclerotium, Trichoderma. The genus Bacillus and gram-negative bacteria were detected in all treatments. The number of fungal colonies was higher than the number of bacterial colonies.